Effect of twisted strips on heat transfer and pressure drop in heat exchangers - Yildiz, C; Bicer, Y; Pehlivan, D (Pergamon-Elsevier Science Ltd, 1998)
Twisted narrow, thin metallic strips were placed in the inner pipe of a concentric double-pipe heat exchanger. Their effects on heat transfer and pressure drop were studied for parallel and countercurrent flow. These turbulators were prepared by twisting the strips through certain angles and designed to touch the inside wall at each step. In the system, hot air was passed through the inner pipe, while cold water was flowing through the annulus. Experiments performed with an empty inner tube confirmed the results with the Dittus-Boelter expression given for the Nusselt number. It was observed that the Nu number could increase up to 100% at a cost of about 130% increase in pressure drop for the tube with twisted strips inside. (C) 1997 Elsevier Science Ltd.
Keywords: heat exchangers; turbulators; effectiveness